English dictionaries as cultural mines - Facchinetti, Roberta, 1967- (Newcastle upon Tyne : Cambridge Scholars, 2012)
Discusses "the role of dictionaries in the identification and expression of cultural aspects in language, with special reference to English. As such, its eleven chapters have been arranged to focus on general, genre-specific, monolingual and bilingual lexicography, both from a diachronic and a synchronic perspective"--Cover, page [4].
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Encyclopedias and dictionaries -- History and criticism; Lexicography; Electronic books